Acute Mediastinitis - Outcomes and Prognostic Factors of Surgical Therapy (A Single-Center Experience) - Vodička, Josef; Geiger, Jan; Židková, Alexandra; Andrle, Pavel; Mírka, Hynek; Svatonˇ, Martin; Kostlivý, Tomáš (Annals of thoracic and cardiovascular surgery, 2022)
PURPOSE: The aims of this work were the retrospective analysis of a cohort of patients with acute mediastinitis treated at the authors' worksite over a 15-year period and the identification of factors that significantly affect the outcomes of the therapy. METHODS: During the period 2006-2020, 80 patients with acute mediastinitis were treated. Within the cohort, the following were observed: the causes and the type of acute mediastinitis, length of anamnesis, comorbidities, diagnostic methods, time from the diagnosis to surgery, types and number of surgical procedures, results of microbiological tests, complications, and outcomes of the treatment. RESULTS: The most common type of acute mediastinitis was descending mediastinitis (48.75%). A total of 116 surgical procedures were performed. Ten patients in the cohort died (12.5%). Patients older than 60 years were at a 6.8 times higher risk of death. Patients with more than two comorbidities were at a 14.3 times higher risk of death. The presence of yeasts in the culture material increased the risk of death by 4.4 times. CONCLUSION: Early diagnosis, removal of the cause of mediastinitis, sufficient mediastinal debridement, and multiple drainage thereof with the possibility of continual postoperative lavage are essential for the successful treatment of acute mediastinitis.
Keywords: Mediastinitis; mediastinitida; drenáž; Prognosis; retrospektivní studie; Humans; výsledek terapie; Acute Disease; lidé; Retrospective Studies; Treatment Outcome; akutní nemoc; Drainage; prognóza